PENYELESAIAN SENGKETA PENERIMA WARALABA DALAM PERJANJIAN WARALABA ANTARA CV. HUTAMA MANDIRI JAYA DAN PT. INDOMARCO PRISMATAMA (STUDI KASUS PUTUSAN NO. 204/Pdt.G/2021/PN Bdg) - Hendra Kurniawan; Rumainur (JOURNAL OF LAW AND NATION, 2025)
The development of franchise businesses has grown rapidly and has become a new force for the domestic economic sector in Indonesia. One example of a franchise business that is in great demand is the minimarket franchise business. PT. Indomarco Pristama is the franchise right holder for the "Indomaret" minimarket. One of the clauses for franchisees who collaborate with PT Indomarco is to receive a cash surplus that must be given to franchisees. However, in one case there was a problem with the agreement. Based on this, the author formulates the problem, namely: 1). What are the franchise regulations according to laws and regulations in Indonesia? 2). How do judges consider franchise disputes based on decision number 204/Pdt.G/2021/PN Bdg? 3). How to resolve franchise disputes between CV. Hutama Mandiri Jaya with PT. Indomarco Prismatama according to decision number 204/Pdt.G/2021/PN Bdg?. By using normative legal research, it was concluded that franchise regulations in Indonesia are regulated in Law Number 40 of 2007 concerning Limited Liability Companies, Government Regulation Number 42 of 2007 concerning Franchising, Minister of Trade Regulation Number 71 of 2019 concerning the Implementation of Franchises. In this case, the judge's consideration was the statement of heir no. 02/LKW/VI/2020 is an authentic deed, the Deed of Establishment of CV. Hutama Mandiri Jaya Number 5 Dated 20 October 2010 is still valid, binding and has legal force recognized by the parties, Deed of Amendmentto Limited Liability Company CV. Hutama Mandiri Jaya Number 12 dated 10 September 2020is legally flawed, not binding and has no legal force. Settlement of franchise disputes between CV. Hutama Mandiri Jaya with PT. Indomarco Prismatama according to decision number 204/Pdt.G/2021/PN Bdg. Sentencing Defendant II dr / Defendant I dk (PT. Indomarco Prismatama) to pay/transfer and hand over all the cash surplus funds of the Indomaret PunclutShop of approximately Rp. 406,430,993.00,- to Plaintiff dr / Defendant II dk immediately and simultaneously; States that due to the Deed of Amendment to the Limited Liability Company CV. Hutama Mandiri Jaya Number 12 dated 10 September 2020 is not legally binding, therefore the Management of Defendant I dr / Plaintiff dk (Wilson Hidayat and William Hidayat) in the Deed is invalid and has no right either jointly or individually to act on name and for the benefit of CV Limited Company. Hutama Mandiri Jaya both inside and outside the Court; Rejecting the Reconvention Plaintiff's Reconvention lawsuit in addition to and in addition. A franchise is a business contract where there is an agreement that cannot be made public. Therefore, it is recommended that if a dispute occurs, it is resolved through negotiationsbetween the disputing parties, either directly or by appointing a legal representative, this is done in order to produce a mutual agreement that benefits both parties. If the negotiation process does not produce an agreement, then the parties submit it to arbitration or court to resolve or decide. Seeing from Decision 204/Pdt.G/2021/PN Bdg, that there is an internal dispute from the franchisee, it is recommended that a clause be added to the agreement if the is a dispute between one of the parties so that it is resolved first internally so as not to harm the other party and still exercise their rights. and obligations in accordance with agreed agreements.